2001
DOI: 10.2337/diabetes.50.11.2585
|View full text |Cite
|
Sign up to set email alerts
|

In Muscle-Specific Lipoprotein Lipase−Overexpressing Mice, Muscle Triglyceride Content Is Increased Without Inhibition of Insulin-Stimulated Whole-Body and Muscle-Specific Glucose Uptake

Abstract: In patients with type 2 diabetes, a strong correlation between accumulation of intramuscular triclycerides (TGs) and insulin resistance has been found. The aim of the present study was to determine whether there is a causal relation between intramuscular TG accumulation and insulin sensitivity. Therefore, in mice with musclespecific overexpression of human lipoprotein lipase (LPL) and control mice, muscle TG content was measured in combination with glucose uptake in vivo, under hyperinsulinemic-euglycemic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
106
3
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 43 publications
5
106
3
1
Order By: Relevance
“…These findings in transgenic rabbits contrast with the results in transgenic mice that showed insulin resistance accompanied by accumulation of TG in their skeletal muscle [16] or liver [4]. Nevertheless, one study reported that there is no effect of the accumulation of TG in skeletal muscle on insulin-stimulated whole-body and muscle-specific glucose uptake [18]. Another study [17] found no difference in the muscle TG contents between musclespecific LPL transgenic and control mice, in spite of transgenic mice having a state of insulin resistance.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…These findings in transgenic rabbits contrast with the results in transgenic mice that showed insulin resistance accompanied by accumulation of TG in their skeletal muscle [16] or liver [4]. Nevertheless, one study reported that there is no effect of the accumulation of TG in skeletal muscle on insulin-stimulated whole-body and muscle-specific glucose uptake [18]. Another study [17] found no difference in the muscle TG contents between musclespecific LPL transgenic and control mice, in spite of transgenic mice having a state of insulin resistance.…”
Section: Discussionmentioning
confidence: 71%
“…However, studies on transgenic mice have also generated conflicting results regarding the effects of LPL on insulin resistance. For example, two studies on LPL transgenic mice have shown that overexpression of human LPL in mouse muscle is associated with insulin resistance [4,17], whereas one group (even using the same transgenic mice as in the above study) failed to show a correlative or causal relationship between increased LPL activity and insulin resistance even though there was increased TG content in the muscles [18]. In addition, one study reported that LPL transgenic mice were protected against diet-induced obesity regardless of slight hyperglycaemia [16].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…lipid-related genes expression Lipid, C. Butyricum LPL is responsible for the hydrolysis of plasma lipoproteins, a rate-limiting step in lipid transport into peripheral tissues (Goldberg, 1996). Overexpression of muscle LPL has been associated with increasing intramuscular triacylglycerol accumulation and fat deposition in mammals (Voshol et al, 2001). Although no significant difference in LPL expression in breast muscle was found in broilers fed the diet supplemented with C. butyricum, a trend toward upregulated LPL gene expression was found, and LPL activity in muscle tissue was significantly increased by C. butyricum addition.…”
Section: Discussionmentioning
confidence: 91%
“…The IMCL content, which in many [1][2][3][4] but not all studies [45,46] has been shown to be increased in insulin resistance, was also one focus of our experiments. The effects of TGRLs on insulin signalling and glucose homeostasis followed a time-dependent fashion.…”
Section: Discussionmentioning
confidence: 96%